UPM hasil buku kaji cabaran dan peluang masyarakat Tamil Melaka - Universiti Putra Malaysia, Pejabat Strategi Korporat dan Komunikasi (Pejabat Strategi Korporat dan Komunikasi, Universiti Putra Malaysia, 2016)
MELAKA – A five-year study on the history and current status of educational, economic, social and religious life of the Tamil-Indians in Melaka has led to the publication of a useful book, highlighting the challenges faced by the community and solutions to the problems.